Kreativiti guru Pendidikan Seni - Chua, Yan Piaw; Md. Nor, Sharifah; Mohd, Naim; Wan Ali, Wan Zah (Universiti Putra Malaysia Press, 2003)
The main purpose of this study is to compare the creativity of trained and untrained art education teachers. This is a descriptive study that uses the Torrance Test of Creative Thinking as its instrument to obtain the creative thinking indexes of the teachers. Subjects of the study comprise 34 trained art education teachers and 45 untrained art education teachers from 22 secondary schools located in the district of Hulu Langat, Selangor. The results of the study indicated that trained art education teachers are significantly more creative than untrained art education teachers in the aspects of fluency and elaboration. This suggests that trained art education teachers can understand creative ideas better and elaborate on them in more detail than untrained art education teachers. The researcher suggests that in future teachers training programmes should place more emphasis on creativity.